Sensory processing: a critical area for understanding autism spectrum disorders - Dunn, Winnie (Henry Stewart Talks, 2020)
Dunn’s sensory processing framework, Core concepts of sensory processing, Tools of Sensory Profile 2, Studies about sensory processing and ASD, Sensory processing and participation, Sensory subtypes and development, Assessment of sensory processing, Some case studies of Sensory Profile 2, Sensory processing within interventions